Hybrid power management for fuel cell-supercapacitor powered hybrid electric vehicle - Babu Arigela, Sri Satya Veerendra (2022)
Fuel cell (FC) with a combination of supercapacitor (SC) based hybrid electric vehicles have been regarded as a potential solution in the future transportation system. This is due to their zero-emission, enhancement of transient power demand, ability to absorb the energy from the regenerative braking, high efficiency, and long mileage. Nevertheless, the nonlinear output characteristics of the FC system are a feeble point owing to internal constraints such as membrane water content and cell temperature. Hence it is essential to extricate as much power as possible from the stack to avert excessive fuel usage and low system efficiency. Conversely, despite the advantages of the SC as an auxiliary energy storage system, the series connection of SC cells causes a cell imbalance problem due to uneven cell characteristics that occur during the manufacturing process and its ambient conditions. This discrepancy of cell voltages in a supercapacitor module leads to reduce the stack’s efficiency and its lifetime. Furthermore, the above limitations of the power sources and initial state of SC’s charge affect the power management’s distribution of power among the multiple sources. Therefore, the aim of this thesis is to propose a hybrid power management for fuel cell-supercapacitor powered hybrid electric vehicles to solve the three identified problems. Firstly, this thesis focuses on a maximum power point tracking (MPPT) controller with a modified 4-leg interleaved boost converter (M-FLIBC) topology for the FC system. The effectiveness of the proposed IBC with a controller for the FC is compared with the two additional controllers couples with the conventional FLIBC topology. Next, a global modular balancer for voltage balancing of multiple supercapacitor cells is connected in series for an HEV system. The global modular balancing architecture is proposed based on forward conversion, which integrates cell balancing, module balancing, and operating for different frequencies. Thus, greatly reducing the volume and implementation complexity. Finally, the thesis evaluates hybrid power management (HPM) for effective power sources distribution, in order to reduce hydrogen consumption and enhance the vehicle's fuel economy. In this case, an equivalent circuit model of SC is developed for the energy storage system. The combination of an extended Kalman filter (EKF) and traditional coulomb counting (CC) method is used to estimate the SC state of charge in improving the effectiveness of the HPM. To evaluate the fuel economy under realistic driving conditions, the combined environmental protection agency (EPA) test cycles for a city and highway are considered. The outcome of performance comparison of the different controllers based on MPPT technique in terms of voltage, current, power, settling time, and efficiency of the FC indicates that the radial basis function network (RBFN) based MPPT controller with the M-FLIBC outperforms the PID and Fuzzy based controllers. With respect to controlling of SC in HEV environment, the proposed topology of SC presents effective voltage balancing with a lower component count, able to operate at different frequencies, i.e., 10 to 70 kHz, as well opens to unlimited stackable modular numbers of SC cells for the HEV performance analysis. Ultimately, with all the proposed control topologies and combined EKF-CC based power management for the FC-SC in Series HEV, the vehicle's fuel economy is increased to 93.38 km/kg as compared to traditional CC based power management of 86.53 km/kg, besides it improves the vehicle’s acceleration within 0-100 km/h in 9.0 seconds respectively. Finally, the research shows that the hybrid power management of FC and SC powered HEV leads to improved performance of the vehicle in terms of the key measures. Suggestions for future research are also highlighted.